Effectiveness of Acceptance and Commitment Therapy on Social Adjustment and Mental health in between Veterans' Girl - Nejat , Ali; Nazari , Golestan; Darabi , Fatemeh; Fakouri Juybari , Zahra (Applied Family Therapy Journal (AFTJ), 2023)
Aim: The purpose of this research is to compare the effectiveness of acceptance and commitment therapy on social adjustment and mental health of children of veterans. Method: This research was a semi-experimental type with a pre-test-post-test design with a control group. The statistical population of this research includes all the female students of veterans who were studying in the second secondary level (198 people). Among this statistical population, 140 people were selected as available, and after the implementation of the mental health questionnaire (GQH-28), 60 people who had more mental health problems (score above 40) were selected purposefully, then randomly divided into two groups. 30 people (two experimental groups and one control group) were replaced. The experimental groups received the intervention based on acceptance and commitment therapy in 8 two-hour sessions, but the control group did not receive any intervention. Before and after the intervention, the tests were performed on the groups, and then the data were analyzed with SPSS 22 software by variance analysis tests with repeated measurements. Results: The findings showed that the treatment based on acceptance and commitment led to an increase in the level of social adaptation (F=159.84, P